PENINGKATAN KEMAMPUAN MENULIS TEKS DESCRIPTIVE DENGAN MODEL PEMBELAJARAN CONSEPT SENTENCE DAN SPLIT DICTATION - Nunik Pujiati (Education Journal : Journal Educational Research and Development, 2017)
Writing text descriptive essentially aims to provide information, describe something that means making other. Knowledge and experience in describing something will train someone to know the material , Gathering details, organizing ideas, and selecting words in writing. This learning model is chosen in the hope of the concept of sentences obtained by students can create text descriptive based on the images presented. The application of split dictation, students are expected to be able to write with the proper spelling. The results showed that the learning model of consept sentence and split dictation can improve the ability to write descriptive text of class VII H SMP Negeri 1 Tugu Trenggalek academic year 2015/2016. The percentage of completeness of classical learning activity in cycle 1 reached 63% with grade average grade 71, while the percentage of classical learning activity cycle 2 reaches 93% with grade average grade 81. There is an increase of classical learning activity 30%. To improve each aspect of descriptive text writing from cycle 1 to cycle 2, there are 10% grammar, 10% vocabulary, 10% content and spelling 15%